2015
DOI: 10.5433/1679-0359.2015v36n6p3763
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in the Haemonchus contortus cuticle exposed to Acacia mearnsii extract

Abstract: The parasite Haemonchus contortus is one of the most pathogenic for small ruminants in tropical and subtropical regions worldwide, including Brazil. The objective of this study was to evaluate the structural changes induced in adult H. contortus after in vitro contact with Acacia mearnsii extract (AE), using scanning electron microscopy. Adult nematodes were collected from a naturally infected lamb. In the in vitro assay the parasites were placed in contact with AE (100 mg ml -1 ), for two hours at 37 o C. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
1
15
0
2
Order By: Relevance
“…Yoshihara et al (2014) required 100 mg mL -1 of a commercial extract of Acacia mearnsii for 97.1% inhibition of larval migration. In addition to the anthelmintic action, the extract caused ultrastructural changes in adult parasites H. contortus after contact in vitro and in vivo (Yoshihara et al, 2015). For flavonoids and tannins, the highest levels were found in the concentration of 3 mg mL -1 .…”
Section: Resultsmentioning
confidence: 97%
“…Yoshihara et al (2014) required 100 mg mL -1 of a commercial extract of Acacia mearnsii for 97.1% inhibition of larval migration. In addition to the anthelmintic action, the extract caused ultrastructural changes in adult parasites H. contortus after contact in vitro and in vivo (Yoshihara et al, 2015). For flavonoids and tannins, the highest levels were found in the concentration of 3 mg mL -1 .…”
Section: Resultsmentioning
confidence: 97%
“…The cuticle of H. contortus was severely deformed following treatment with Acacia mearnsii extract (Yoshihara et al, 2015). Millettia pachycarpa root bark extract also caused damaging effects on the cuticle of A. galli, including shrinkage and collapse of the lips (Lalchhandama, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…25 Natural cysteine proteinases also exert anthelmintic activity by primarily attacking the cuticle in different roundworms. 26,27 Extract of Acacia mearnsii was shown to cause shrinkage and severe destruction on the cuticle of H. contortus 28 . We have also shown that a related plant Acacia oxyphylla extract primarily acted through the cuticle to cause tissue damages in the internal musculature in A. galli.…”
Section: Discussion/conclusionmentioning
confidence: 99%